(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2017)
Like other countries the epics constitute an important aspect of the Sanskrit literature in India. Two important epics were produced during the ancient times viz. Mahabharata and Ramayana. These epics or long poems originated from the heroic stories sung at the time of great sacrifices during the Vedic age.It may be noted that these epics were not written at one time by any single author and they were touched and retouched by different writers from time to time. Usually the authorship of Ramayana is assigned to Valmiki and that of Mahabharata to Vedavyasa.The Ramayana is known as the Adikavya (the earliest narrative poem). It contains 24,000 verses and is divided into seven books. The work deals with the central theme of the conflict between Rama and Ravana in a simple and direct form without indulging in the literary gymnastics so common among later classi¬cal writers.